Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jobm.201800318
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex and quantitative PCR targeting SCAR markers for strain‐level detection and quantification of biofertilizers

Abstract: Biofertilizers are the eco‐friendly bio‐input being used to sustain the agriculture by reducing the chemical inputs and improving the soil health. Quality is the major concern of biofertilizer technology which often leads to poor performance in the field and thereby loses the farmers’ faith. To authenticate the strain as well as its presumed cell load of a commercial product, sequence characterized amplified region (SCAR) markers were developed for three biofertilizer strains viz., Azospirillum brasilense (Sp7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Molecular biology offers techniques for detecting the presence and abundance of specific microorganisms whether in the soil, rhizosphere or in a commercial inoculant, with high sensitivity. Sequence Characterized Amplified Region (SCAR) marker-based fingerprinting produces very good results as demonstrated by a recent research we carried out (Reddypriya et al, 2019) and those of Couillerot et al (2010) and Reddypriya et al (2016). Our results showed that, in addition to authentication, quantitative PCR and SCAR marker allow for assessing the cell loads per g/ml of inoculants (Figure 2).…”
Section: Techniques' For Strain Identificationmentioning
confidence: 56%
See 1 more Smart Citation
“…Molecular biology offers techniques for detecting the presence and abundance of specific microorganisms whether in the soil, rhizosphere or in a commercial inoculant, with high sensitivity. Sequence Characterized Amplified Region (SCAR) marker-based fingerprinting produces very good results as demonstrated by a recent research we carried out (Reddypriya et al, 2019) and those of Couillerot et al (2010) and Reddypriya et al (2016). Our results showed that, in addition to authentication, quantitative PCR and SCAR marker allow for assessing the cell loads per g/ml of inoculants (Figure 2).…”
Section: Techniques' For Strain Identificationmentioning
confidence: 56%
“…IAA is one of the main phytohormone enhancing plant growth by stimulating the elongation of stems FIGURE 2 | PCR targeting SCAR markers of biofertilizer strains for strain-level authentication and qualification in maize rhizosphere at different growth stages 15th (A), 30th (B), and 60th (C) day. Error bar indicates with letters "a" and "b" (ANOVA and DMRT test; p < 0.05) (Reddypriya et al, 2019) Reproduced with permission.…”
Section: Potential Features Of Phosphate Solubilizing Actinobacteriamentioning
confidence: 99%
“…Comparable PCR-based approaches to those proposed in this study have also been reported. Three primer sets targeting sequence characterized amplified region (SCAR) markers were designed and implemented for endpoint and qPCR assays for the quality control of a biofertilizer consortium composed of Azotobacter chroococcum , Bacillus megaterium and Azospirillum brasilense strains [ 19 ]. While authors described this method as reliable for field applications, once the designed primer sequences are subjected to BLASTn in silico analyses, cross reactivity and false positive biases with other plant–soil associated bacteria are found.…”
Section: Discussionmentioning
confidence: 99%
“…SCAR marker‐based detection cannot differentiate between live and dead cells. This would not be a significant issue since dead cell DNA will not remain stable for a longer duration in an environment [16]. Besides these trivial constraints, numerous reports on microbial SCAR markers are due to their advantageous position amidst other pre‐existing techniques.…”
Section: Constraints In Scar Marker Technologymentioning
confidence: 99%
“…Sequence characterized amplified region (SCAR) marker ensures rapid molecular detection and quantification of microbial strains based on their inherent genetic variability. Locus-specific SCAR markers have been identified and reported for several biocontrol agents and biofertilizers worldwide [15][16][17][18]. Similarly, there are multiple reports on the success of microbial SCAR markers in precise pathogen detection [19][20][21].…”
Section: Introductionmentioning
confidence: 99%